PENGGUNAAN MODEL PEMBELAJARAN CONTXTUAL TEACHING AND LEARNING BERBANTUAN CONGKLAK UNTUK MENINGKATKAN KEMAMPUAN OPERASI HITUNG PENJUMLAHAN - Nurmitasari Nurmitasari; Defry Eza Ramadhan; Febri Liani; Imelta Intan Muspika; Adinda Dewi Andini; Vitara Dewi Nazarina (LPPM Universitas Cipta Mandiri, 2026)
Mathematics learning in elementary school, especially addition arithmetic operations, is still a challenge for first-grade students. The results of pre-research at UPT SD Negeri 1 Fajar Agung Pariaman showed that only 42% of students completed the learning. This study aims to analyze the effect of the Contextual Teaching and Learning (CTL) learning model assisted by congklak on the ability of addition arithmetic operations. The method used is quantitative with a Post test only control group design. The population in this study was 50 first-grade students at UPT SD Negeri 1 Fajar Agun, consisting of 25 students in the experimental class and 25 students in the control class. The research instrument was a descriptive learning outcome test, data analysis included validity, reliability, normality, homogeneity and t-test tests. The results of this study indicate that there is a significant difference between the learning outcomes of students taught using the CTL model assisted by congklak and conventional learning. The average learning outcomes of the experimental class were higher than those of the control class, so the CTL model assisted by congklak effectively improves students' addition arithmetic operations.